Islamic Law in the Islamic Sultanates of Indonesia: Historical Patterns and Legal Transformations - Fakhriyah Annisa Afroo; Asasriwarni; Ikhwan (AN NUR: Jurnal Studi Islam, 2025)
This article examines the characteristics and transformations of Islamic law in the Islamic sultanates of Indonesia through a historical-normative approach combined with comparative analysis. The study aims to identify patterns of Islamic law implementation and to analyze its dynamic relationship with customary law (adat) and political authority during the pre-colonial period. Data were collected through library-based research, including legal manuscripts, royal chronicles, customary texts, and relevant scholarly literature. The findings demonstrate that Islamic law in the Islamic sultanates of Indonesia did not develop as a uniform or rigid system, but rather evolved in diverse, contextual, and adaptive forms. Four main models of Islamic law implementation are identified: normative-social, normative-formal, integrative adat–sharia, and legal codification models. These variations were shaped by local social structures, political authority, and indigenous legal traditions within each sultanate. The study further reveals that from its early development, Islamic law in Indonesia operated within a framework of legal pluralism through continuous processes of negotiation and accommodation. This research contributes to a deeper historical understanding of the foundations of contemporary Islamic law in Indonesia.